Evaluation of Constructivism Approach in Blended Learning at Universitas Pendidikan Mandalika - kholisussa'di, Kholisussa'di; Lestari, Gunarti Dwi; Susilo, Heryanto (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2025)
The constructivist approach provides a strong theoretical framework for creating meaningful learning, in which students not only passively receive information, but also actively engage in the process of exploration and problem-solving. In the context of blended learning at UNDIKMA, the application of this approach requires effective learning design, active collaboration between lecturers and students, and optimal use of technology. The main purpose of this study is to obtain information about the methods used in implementing blended learning using e-learning. This study uses a descriptive quantitative approach, which aims to describe the phenomenon of implementing e-learning-based blended learning at the Mandalika Education University (UNDIKMA). The results of the study are that lecturers at UNDIKMA are quite successful in compiling and delivering learning materials, providing clear references, and creating a conducive and fun learning atmosphere. Most students feel that the learning they receive is relevant to the latest developments and is contextual in nature, which is important to enhance their understanding of a particular field of study.Key Words: Constructivism, Blended Learning